Experimental Study on Seepage Anisotropy of a Hexagonal Columnar Jointed Rock Mass - Yanxin He; Zhende Zhu; Wenbin Lu; Yuan Tian; Xinghua Xie; Sijing Wang (Shock and Vibration)
Many columnar jointed rock masses (basalt) are present at the Baihetan hydropower dam site, and their seepage characteristics have a significant impact on the project’s safety and stability. In this study, model samples consisting of material similar to the columnar jointed rock mass with different inclination angles (0°–90°) were prepared and laboratory triaxial seepage tests were performed to study the seepage characteristics of the columnar jointed rock mass under maximum axial principal stress. The experimental results showed that the similar material model samples of columnar jointed rock mass showed obvious seepage anisotropy. The nonlinear seepage characteristics were well described by the Forchheimer and Izbash equations, and the fitting coefficients of the two equations were in good correspondence. The curves describing the relationship between the inherent permeability and the stress of the samples with different dip angles were U-shaped and L-shaped, and a one-variable cubic equation well described the relationship. The 45° angle specimen had the highest sensitivity to the maximum principal stress, and its final permeability increased by 144.25% compared with the initial permeability. The research results can provide theoretical support for the stability evaluation of the Baihetan hydropower station.